CO-INFECTION OF BOVINE PAPULAR STOMATITIS VIRUS, ROTAVIRUS AND CRYPTOSPORIDIUM SPP. IN A CALF - Eroksuz, Yesari; Timurkan, Mehmet Ozkan; Abayli, Hasan; Incili, Canan Akdeniz; Karabulut, Burak; Eroksuz, Hatice (Sciendo, 2020)
Concurrent occurence of bovine papular stomatitis, rotavirus infection and cryptosporidiosis was diagnosed postmortem in a 7-days-old calf from a farm containing 65 calves of different ages. Multifocal papular stomatitis and rumenitis were present on necropsy. While polymerase chain reaction analysis revealed rotavirus and papular stomatitis virus infections; bovine viral diarrhea, foot and mouth disease, bovine papilloma virus and coronavirus could not be detected. Overall; concurrent co- infection with bovine papular stomatitis virus, rotavirus and Cryptosporidium spp. was reported for the first time.
Keywords: Bovine papular stomatitis; rotavirus; cryptosporidiosis